Zmienność zadań i przedmiotu kontroli marketingowej w kontekście oceny jej funkcjonowania - Kowal, Witold (The Variability of the Task and Subjects of the Control of Marketing Effectiveness, 2008)
The aim of this paper is to present the results of observations, which focused on the effectiveness as a task of marketing control. The results demonstrated that strategic effectiveness is the most important task of marketing control, and operational effectiveness is the last important. The main roles in the effectiveness control play: sales, market share, customer satisfaction and customer loyalty. The results demonstrated that the task and subjects of marketing control are the same.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 195-206